Immunotoxicity assessment of CdSe/ZnS quantum dots in macrophages, lymphocytes and BALB/c mice - Wang, Xiaomei (2016)
Background: The toxicity of CdSe/ZnS quantum dots (QDs) in the environment and biological systems has become a major concern for the nanoparticle community. However, the potential toxicity of QDs on immune cells and its corresponding immune functions remains poorly understood. In this study, we investigated the immunotoxicity of CdSe/ZnS QDs using the in vitro in macrophages and lymphocytes and in vivo in BALB/c mice. Results: Our results indicated that macrophages treated with 1.25 or 2.5 nM QDs exhibited decreased cell viability, increased levels of reactive oxygen species (ROS), elevated apoptotic events, altered phagocytic ability, and decreased release of TNF-α and IL-6 by upon subsequent stimulation with Lipopolysaccharide (LPS). In contrast, lymphocytes exposed to QDs exhibited enhanced cell viability, increased release of TNF-α and IL-6 following exposure with CpG-ODN, and decreased transformation ability treatment in response to LPS. To study the in vivo effects in mice, we showed that QDs injection did not cause significant changes to body weight, hematology, organ histology, and phagocytic function of peritoneal macrophages in QDs-treated mice. In addition, the QDs formulation accumulated in major immune organs for more than 42 days. Lymphocytes from QDs-treated mice showed reduced cell viability, changed subtype proportions, increased TNF-α and IL-6 release, and reduced transformation ability in response to LPS. Conclusions: Taken together, these results suggested that exposures to CdSe/ZnS QDs could suppress immune-defense against foreign stimuli, which in turn could result in increased susceptibility of hosts to diseases.